2020
DOI: 10.1136/bmjgh-2020-002516
|View full text |Cite
|
Sign up to set email alerts
|

Time trends and determinants of breastfeeding practices among adolescents and young women in Nigeria, 2003–2018

Abstract: IntroductionOptimal breastfeeding practices have far-reaching health and economic benefits. Evidence suggests disparities in breastfeeding practices by maternal age-groups, with younger mothers often having lower rates of breastfeeding initiation, continuation and exclusivity compared with older mothers. There is limited knowledge of trends and factors associated with breastfeeding practices, particularly among adolescent and younger mothers in Nigeria. We examine key breastfeeding practices in Nigeria over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 96 publications
8
34
0
1
Order By: Relevance
“…Our study found that adolescent mothers aged <18 years reported a decreased likelihood of EIBF compared to those aged 18–19 years. This finding was consistent with a cross-sectional study conducted in Nigeria which found that EIBF among adolescent mothers aged 12–18 years reduced by the crude odds of 36% compared with young women (20–24.9 years) [ 38 ]. Younger mothers lack experience, education, attitude and the necessary social support required for the appropriate breastfeeding practices [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study found that adolescent mothers aged <18 years reported a decreased likelihood of EIBF compared to those aged 18–19 years. This finding was consistent with a cross-sectional study conducted in Nigeria which found that EIBF among adolescent mothers aged 12–18 years reduced by the crude odds of 36% compared with young women (20–24.9 years) [ 38 ]. Younger mothers lack experience, education, attitude and the necessary social support required for the appropriate breastfeeding practices [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…It was observed that adolescent mothers who had no ANC visit during pregnancy reported delayed initiation of breastfeeding. This finding supported a cross-sectional study conducted in Bangladesh [ 18 ] and India [ 23 ] that no ANC visit during pregnancy was less likely to EIBF but contradicts a cross-sectional study that examined trends and factors associated with breastfeeding practices among adolescent and younger mothers in Nigeria that found adolescent mothers who had ANC were less likely to delay breastfeeding initiation [ 38 ]. A past study conducted in Bangladesh indicated that among women that had ANC, about half of them were accompanied by their partners/husbands to the health facility [ 40 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…31 , 41 However, mothers who deliver at home are less likely to realize the importance of exclusive breastfeeding and the harms of pre-lacteal feeding as they are supported by a conventional birth attendant who promotes the practice of prelacteal feeding. Even, in line with a study conducted in Eastern Ethiopia, 53 Nigeria, 54 and Pakistan. 6 In this study, delayed initiation of ANC visits was more likely to practice prelacteal feeding in Eastern Africa in line with other studies.…”
Section: Discussionsupporting
confidence: 86%
“…Yoruba, Igala, Tiv; and 4. Other) [34], highest level of maternal education (no education; incomplete primary/completed primary; incomplete secondary/completed secondary; higher), maternal age group at the time of the birth (<20; 20-24.9; 25-29.9; 30-34.9; >35), marital status at the time of survey (married/cohabiting or not), wantedness of pregnancy (wanted at the time or unwanted/mistimed), sex of the baby (male; female), birthweight ('very small/ small', 'average' or 'larger than average'), type of pregnancy (singleton; multiple), parity at last live birth (0, 1-3, 4+), place of birth (public primary, public hospital, private facilities), referral during childbirth (yes/no), and number of antenatal visits (none, 1-3, 4-7, 8+). The household wealth index score was calculated using principal component analysis on the basis of household assets and household characteristics.…”
Section: Outcomes and Explanatory Variablesmentioning
confidence: 99%